Pain and Moderate to Vigorous Physical Activity in Adolescence: An International Population-Based Survey. Issue 5 (5th February 2016) - Swain, Michael Steven; Henschke, Nicholas; Kamper, Steven James; Gobina, Inese; Ottová-Jordan, Veronika; Maher, Christopher Gerard
Abstract : Objective. To evaluate whether individual types of pain (headache, stomach-ache, and backache) or multiple pains affect the odds of young people achieving the recommended 60 minutes of moderate to vigorous physical activity (MVPA) per day in a large representative sample. Design. Multicenter cross-sectional survey. Setting. Twenty-eight countries across Europe and North America. Subjects. Adolescents (N = 242, 103). Methods. An analysis of data collected in two waves (2001/02 and 2005/06) of the health behavior in school-aged children (HBSC) study was performed. Survey questions included the HBSC symptoms checklist and the amount of regular physical activity. Multilevel logistic regression was used to account for clustering effect of MVPA within countries. Models investigated the relationship between pain and physical activity, adjusted for the HBSC study year. Six models were conducted separately for gender and age-group (11, 13, and 15 years) strata. Results. In general, the presence of pain was associated with reduced physical activity. Headache alone was associated with reduced physical activity in all six strata (odd ratios 0.77–0.84), stomach-ache alone in five strata (0.77–0.92), and backache alone in four strata (0.86–0.96). In 11- and 13-year-old girls, headache, stomach-ache, and backache, individually and in combination, were associated with decreased odds of being physically active (odds ratios ranging from 0.73 to 0.91). Within the other four age and gender strata, the relationship was less consistent. Conclusion. Pain is associated with reduced physical activity in adolescents but this association varies according to gender, age, and the type of pain experienced.